2000
DOI: 10.1111/j.1348-0421.2000.tb02486.x
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Bifidobacterium lactis (HN019) Enhances Resistance to Oral Salmonella typhimurium Infection in Mice

Abstract: The ability of a newly identified probiotic lactic acid bacterial strain, Bifidobacterium lactis (HN019), to confer protection against Salmonella typhimurium was investigated in BALB/c mice. Feeding mice with B. lactis conferred a significant degree of protection against single or multiple oral challenge with virulent S. typhimurium, in comparison to control mice that did not receive B. lactis. Protection included a ten-fold increase in survival rate, significantly higher post-challenge food intake and weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
87
0
4

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 21 publications
12
87
0
4
Order By: Relevance
“…In particular, Bi®dobacterium lactis (strain HN019, DR10 TM ) has been shown to enhance phagocytic cell function and the production of interferongamma (IFNg) in laboratory animals, and to increase immune-mediated resistance in mice to challenge with a virulent strain of Salmonella typhimurium (Gill, 1998;Gill et al, 1999;Shu et al, 1999). In the present study, we report the immunomodulatory effects of dietary B. lactis HN019 in healthy elderly subjects.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In particular, Bi®dobacterium lactis (strain HN019, DR10 TM ) has been shown to enhance phagocytic cell function and the production of interferongamma (IFNg) in laboratory animals, and to increase immune-mediated resistance in mice to challenge with a virulent strain of Salmonella typhimurium (Gill, 1998;Gill et al, 1999;Shu et al, 1999). In the present study, we report the immunomodulatory effects of dietary B. lactis HN019 in healthy elderly subjects.…”
Section: Introductionmentioning
confidence: 57%
“…Previous studies have indicated that dietary consumption of some strains of LAB can signi®cantly enhance host resistance to GI-tract infections, and subsequently reduce clinical recovery times Majamaa et al, 1995;Saxelin, 1997). The strain of B. lactis used here (HN019) has recently been shown to enhance phagocytic cell function and increase resistance in mice to infection with Salmonella typhimurium (Shu et al, 1999), further indicating that dietary consumption of probiotic LAB has the potential to offer signi®cant immune-mediated improvements in health.…”
Section: Discussionmentioning
confidence: 99%
“…While it is dif®cult to correlate a proven health bene®t in humans with a measurable increase in immune function, there is some circumstantial evidence to support the case with probiotic LAB, since dietary consumption of live yoghurt cultures has been shown to reduce intestinal viral infections, and may also reduce tumour growth (Saavedra et al, 1994;Sawamura et al, 1994;Aso et al, 1995;Majamaa et al, 1995;Rafter, 1995). In previous studies, we have demonstrated that dietary consumption of B. lactis can enhance cellular immune function in mice (Gill, 1998;Gill et al, 2000) and that this enhancement correlates with increased resistance to intestinal infection with Salmonella typhimurium (Shu et al, 2000); there is therefore the promising possibility that enhancement of immune function by dietary consumption of B. lactis might also provide disease protection in humans, however this remains to be determined.…”
Section: Discussionmentioning
confidence: 81%
“…2,3) Furthermore, several reports have revealed that these probiotics can act in helping to protect from intestinal infections, 4,5) alter immunostimulation 6) and decrease elevated serum levels of cholesterol 7,8) and glucose 8-10) on several animal models. There have been several recent reports on regulation of allergic antibody production.…”
mentioning
confidence: 99%